Splenic Artery Embolization and Splenectomy for Spontaneous Rupture of Splenic Hemangioma and Its Imaging Features - Lin, Jia-Li; Lin, Can; Wang, Han-Lu; Wu, Shao-Jie; Tang, Yi; Yang, Chang Shun; Luo, Jie-Wei; Chi, Wu; Fang, Zhu-Ting (Frontiers in Cardiovascular Medicine, 2022)
Background: Spontaneous splenic rupture (SSR) is a rare, often life-threatening, acute abdominal injury that requires immediate diagnosis and early treatment. SSR is mainly treated surgically or conservatively. Case presentation: A 30-year-old male patient complaining mainly of left upper abdominal pain underwent emergency abdominal computed tomography (CT) and showed enlargement of the spleen with a massive mixed-density shadow approximately 10.0 × 8.0 × 12.5 cm in size. The boundary was unclear and showed obvious progressive enhancement. Considering the intrasplenic tumor lesions with rupture and hemorrhage, the possibility of vascular tumors was high, with intraperitoneal blood and fluid accumulation. Digital subtraction angiography of the splenic arteriography and embolization of the ruptured splenic artery branches were performed. Postoperative hemoglobin progressively decreased, inflammatory indicators, such as white blood cell counts, PCT, and CRP were significantly increased, and two days after embolization, the patient developed severe hypoxemia, shock, pulmonary edema, and acute respiratory distress syndrome. CT re-examination nine days after embolization showed reduced lesion absorption. After stabilization of the condition, splenectomy was performed, and postoperative platelet count increase, anticoagulant improvement, and discharge were observed. Postoperative pathological examination revealed extensive hemorrhage and necrosis, vascular tissue with abnormal hyperplasia in the surrounding area, vascular tissue in the bleeding area and outer wall (elastic fiber staining +), and local myofibroblast hyperplasia. Immunohistochemistry showed actin (SM +) and Ki67 (10% +). Conclusion: SSR caused by splenic hemangioma is rare, and the choice between surgical treatment or splenic artery embolization remains dependent on the patient's hemodynamic stability and imaging findings.